The Role of Islamic Education in Improving Adolescent Social Skills - Hilmi, Fuad (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2026)
Islamic education has a strategic role in shaping adolescent social skills based on religious and moral values. This study aims to examine how Islamic education contributes to fostering adolescent social skills, especially in the aspects of communication, cooperation, tolerance, and social responsibility. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation studies. The subjects of the study included educators, education personnel, and students at the secondary level. The results of the study indicate that Islamic education, through the integration of faith, morality, and social values in the learning process, is effective in developing adolescents’ abilities to interact positively in their social environment. The value education instilled in Islamic Religious Education (PAI) encourages adolescents to be empathetic, respect differences, and actively participate in social activities. In conclusion, Islamic education is an important foundation in fostering adolescent social skills, so it needs to be continuously strengthened through a contextual and applicable approach.